Implementasi Metode Hot Fit Dalam Evaluasi Kesiapan Pengguna Sistem Informasi Akademik Terintegrasi - Vivi Safitri (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2016)
- Integrated Information System can provide support in providing data and information that integrates all of the organizational unit concerned. Implementation of an integrated information system in an organization will bring a change in the organization. Acceptance and rejection of the adoption and implementation of the Information System will occur and the turmoil in the organization. To see the extent of the readiness of the adoption of an integrated information system that required an evaluation of the process. Variable Human, Organization and Technology is essential and fundamental that influence the successful adoption and implementation of information systems in an organization. In this study, the method used is the method HOT fit, this model puts an important component in the information system that is human, organization and technology and the suitability of the relationship such as the determinants for the successful adoption and implementation of a system integrated information Academic Affairs College. Analysis will be done through hypothesis testing, Test Validity and Reliability. Results of the analysis will be described in terms of quantitative tests that have been carried out.